Making governance work against radicalisation - Aziz Al-Azmeh (Danish Institute for International Studies (DIIS), 2006)
The connection between governance and radicalization is explored in this working paper. Radicalisation requires a number of political and socio-economic conditions. In order to be effective and not remain confined to sub-cultural margins, radicalisation also requires infrastructural capacities in the forms of finance, organisational networks, and guiding ideas, perceptions and political ideologies. Counter radicalisation policy must take account of longterm developments and prospects, and must be concretely related to matters in the field which is complex and continuously changing.
Keywords: 330; Radikalismus; Politische Gewalt; Islam; Governance-Ansatz